Induction of phenolic compounds by UV and PAR is modulated by leaf ontogeny and barley genotype - Holub, Petr; Nezval, Jakub; Štroch, Michal; Špunda, Vladimír; Urban, Otmar; Jansen, Marcel A K; Klem, Karel (Plant physiology and biochemistry, 2019)
We investigated the effect of leaf ontogeny and barley genotype on the accumulation of phenolic compounds (PhCs) induced by ultraviolet (UV) and photosynthetically active radiation (PAR). We hypothesized that different groups of PhCs are induced in leaves differing in ontogeny, and that this has consequences for protective functions and the need for other protection mechanisms. Generally, lower constitutive contents of PhCs (under conditions of UV exclusion and reduced PAR) were found in a UV-sensitive genotype (Barke) compared to a tolerant genotype (Bonus). However, UV and PAR induced accumulation of PhCs exceeded the constitutive amounts several fold. Specifically, lutonarin, 3-feruloylquinic acid, unidentified hydroxycinnamic acid and luteolin derivatives were markedly enhanced by high PAR and UV irradiances. Leaves developed during UV and PAR treatments had higher PhCs contents than mature leaves already fully developed at the onset of the UV and PAR treatment. UV and PAR treatments had, however, a minor effect on saponarin and unidentified apigenin derivatives which occur particularly in mature leaves of the tolerant genotype Bonus. In addition, high UV and PAR intensities increased the total content of xanthophylls (VAZ), while chlorophyll content was reduced, particularly in developing leaves. A redundancy analysis revealed positive associations between most of PhCs and VAZ and a negative association between total chlorophylls and carotenoids. Non-linear relationships between VAZ and lutonarin and other PhCs indicate that VAZ accumulation can compensate for the insufficient efficiency of anti-oxidative protection mediated by PhCs. Accordingly, we conclude that UV and PAR-induced accumulation of PhCs is affected by leaf ontogeny, however, this effect is compound-specific.
Keywords: listy rostlin; xanthofyly; Genotype; Hordeum vulgare; Hordeum; Leaf age; Chlorophyll; Xanthophyll cycle; Secondary metabolites; Photoprotection; flavonoly; fenoly; ultrafialové záření; chlorofyl; Flavonols; Ultraviolet radiation; Light irradiance; Carotenoids; ječmen (rod); Plant Leaves; Ultraviolet Rays; genotyp; Phenols; Xanthophylls; karotenoidy